MiR‐378a‐3p as a putative biomarker for hepatocellular carcinoma diagnosis and prognosis: Computational screening with experimental validation. Issue 2 (14th February 2021) - Qian, Fuliang; Wang, Jinghan; Wang, Ying; Gao, Qian; Yan, Wenying; Lin, Yuxin; Shen, Li; Xie, Yufeng; Jiang, Xiaoqing; Shen, Bairong
Abstract: Background: Hepatocellular carcinoma (HCC) is a malignant disease with high morbidity and mortality, and the molecular mechanism for the genesis and progression is complex and heterogeneous. Biomarker discovery is crucial for the personalized and precision treatment of HCC. The accumulation of reported microRNA biomarkers makes it possible to combine computational identification with experimental validation to accelerate the discovery of novel biomarker. Results: In the present work, we applied a rational computer‐aided biomarker discovery model to screen for the HCC diagnosis biomarker. Two HCC‐associated networks were constructed based on the microRNA and mRNA expression profiles, and the potential microRNA biomarkers were identified based on their unique regulatory and influential power in the network. These putative biomarkers were then experimentally validated. One prominent example among these identified biomarkers is MiR‐378a‐3p: It was shown to independently regulate several important transcription factors such as PLAGL2 and β‐catenin, affecting the β‐catenin signaling. Such mechanism may indicate a potential tumor suppressor role of MiR‐378a‐3p and the impact of its abnormal expression on the cell growth and invasion of HCC. Conclusions: A bioinformatics model with network topological and functional characterization was successfully applied to the identification of HCC biomarkers. The predicted microRNA biomarkers were than validated with experiments using human HCC cell lines, model animal, and clinical specimens. The results confirmed the prediction by our proposed model that miR‐378a‐3p was a putative biomarker for diagnosis and prognosis of HCC. Abstract : A rational computer‐aided biomarker discovery model has been successfully applied to screen microRNA biomarker for hepatocellular carcinoma based on their unique regulatory and influential power in the microRNA‐mRNA network. MiR‐378a‐3p was identified and validated as a biomarker for HCC diagnosis and prognosis, it was shown independently regulated several important transcription factors including PLAGL2 and β‐catenin, then affected the β‐catenin signaling, which could be the potential mechanism for its function as a tumor suppressor and its abnormal expression could affect the cell growth and invasion of HCC